Core-shell fluorine-based resin particles having improved flowability and cohesiveness, and method for preparing same
By emulsifying the polymerization of acrylic monomers in the perfluorinated polymer particle slurry and using a specific emulsifier, core-shell particles of perfluorinated resin core and polymethyl methacrylate-based resin shell were prepared, which solved the problems of insufficient fluidity and increased cohesion in the prior art, and achieved low cohesion and excellent dispersion.
Patent Information
- Application Number
- CN202380056524.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-29
- Filing Date
- 2023-05-03
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-05-03
AI Technical Summary
In actual use, existing core-shell particles have problems such as insufficient fluidity and increased cohesion, which leads to insufficient fluidity of the slurry and limits the full performance of their performance.
Core-shell particles having a perfluorinated resin core and a polymethyl methacrylate-based resin shell are prepared by emulsifying the polymerized acrylic monomer in a perfluorinated polymer particle slurry and using polyethylene glycol ether having C8 or more alkyl groups as an emulsifier.
Low cohesion between particles, excellent dispersion and uniform particle size are achieved, and the adhesive force can be adjusted to provide uniform adhesive characteristics.
Smart Images

Figure CN119630719A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a dispersion comprising core-shell type fluorine-based resin particles having improved fluidity and cohesion.
[0002] An embodiment of the present invention provides a particle having a perfluorinated polymer core and an acrylic polymer shell, a mixture or slurry (dispersion) containing the particle, and a preparation method thereof. The particle is prepared by adding acrylic monomers to a perfluorinated polymer particle dispersion.
[0003] In the core-shell type particles having a perfluorinated resin core and a polymethyl methacrylate-based resin shell prepared by the method, the shell resin well wraps the entire surface of the core with a uniform thickness.
[0004] In addition, the core-shell type particles are characterized by having a uniform particle size, excellent fluidity and low cohesion, and the PTFE fibrillation time point can be controlled according to the user's intention. Background Art
[0005] Perfluorinated polymers including polytetrafluoroethylene (PTFE) have the following uses: Due to their electrical properties, thermal properties, and adhesive properties, they are used in various adhesives, process improvers, and fluidizing agents; or in coatings for semiconductor manufacturing equipment, coating materials for various substrates in power storage devices, and as adhesive materials for use with other materials.
[0006] However, the adhesion of the perfluorinated resin particles themselves to other materials (polymer resin films or electrodes, etc.) is still insufficient. In order to solve this problem and improve the surface properties while making full use of the properties of the perfluorinated resin particles, a preparation technology for core-shell particles with a non-fluorinated resin shell layer as the surface layer of the fluorinated resin particles has been developed.
[0007] However, for existing core-shell particles, the increase in cohesion is greater than that in dispersibility, so in actual use, the fluidity of the slurry is insufficient, and due to the cohesion between the particles, it is limited in terms of exerting sufficient performance. In addition, it is difficult to obtain a shell layer uniformly formed on the entire surface of the perfluorinated resin particle (core), so it is difficult to adjust the physical properties. Summary of the invention
[0008] Problem that the invention aims to solve
[0009] In order to solve the above-mentioned problem, an implementation example of the present invention provides a core-shell particle, wherein the core-shell particle comprises a perfluorinated resin core having excellent dispersibility and a polymethyl methacrylate-based resin shell. The provided core-shell particle uses a powder rheometer FT4 of Freeman Technology. After the core-shell resin is filled in a sample tube having a diameter of 50 mm, the impeller is rotated at a tip speed of 100 mm / s and descends at the same time, and the total energy is measured 11 times. When the cohesion energy is measured during the ascending process, the specific energy (cohesion energy) is less than 10 mJ / g, and the total energy (Total energy) is less than 2000 mJ.
[0010] Therefore, the core-shell particles of one embodiment provide a core-shell particle having a perfluorinated resin core with low cohesion between particles and an acrylic polymer shell.
[0011] In addition, the purpose of the core-shell particles of an implementation example is to provide a core-shell particle having a particle size of 100 nm to 500 nm, comprising a perfluorinated resin core and a polymethyl methacrylate-based resin shell.
[0012] In addition, the core-shell particles according to one embodiment provide an excellent particle shape in which the shell layer uniformly covers the entire area of the core.
[0013] Means used to solve problems
[0014] As a result of research conducted to solve the above-mentioned problem, it was found that in a perfluorinated polymer particle slurry, core-shell polymer particles and a slurry containing the same are prepared by emulsion polymerization of acrylic acid-based monomers, and as an emulsifier, polyethylene glycol ether (polyethylene glycol ether) having an alkyl group of C8 or above substituted with one or more alkyl groups of the following chemical formula 1 is used as an emulsifier for emulsion polymerization, thereby preparing core-shell particles having the above-mentioned physical properties and a mixture or slurry containing the same, thereby completing the present invention.
[0015] [Chemical formula 1]
[0016] R-(-O-C2H4-) n -OH
[0017] (Wherein, in the chemical formula, R is an alkyl group of C8 or more substituted by one or more alkyl groups, and n is an integer from 5 to 15.)
[0018] As an implementation example, the R may be C8 to C 30 An alkyl group substituted with one or more alkyl groups.
[0019] In the chemical formula 1 of an implementation example, the ratio of the molecular weight of the oxyethylene group as the hydrophilic group to the total molecular weight ([oxyethylene chain molecular weight] / [total molecular weight]) of the composite core-shell particle slurry may be 0.5 to 1.0.
[0020] As an implementation example, the chemical formula 1 may be the following chemical formula 2.
[0021] [Chemical formula 2]
[0022]
[0023] As an implementation example, the core-shell particles having the perfluorinated polymer core and the acrylic polymer shell are prepared by emulsifying and polymerizing acrylic monomers in a seed slurry containing perfluorinated particles (hereinafter referred to as "perfluorinated resin particle slurry") using the polyethylene glycol ether having a C8 or higher alkyl group substituted with one or more alkyl groups of the chemical formula 1 as an emulsifier.
[0024] As an implementation example, the perfluorinated resin particle slurry may contain tetrafluoroethylene-derived units as a main component.
[0025] As an example of the composite core-shell particle slurry, the polymethyl methacrylate-based resin shell layer may contain 60 wt % or more.
[0026] In one implementation example, the core-shell particles and slurry having a perfluorinated resin core-polymethyl methacrylate-based resin shell can be prepared by using a polyethylene glycol ether having an alkyl group of C8 or above substituted with one or more alkyl groups of the following chemical formula 1 as an emulsifier in the perfluorinated resin particle slurry and by emulsifying and polymerizing an acrylic acid-based monomer.
[0027] [Chemical formula 1]
[0028] R-(-O-C2H4-) n -OH
[0029] (Wherein, in the chemical formula, R is an alkyl group of C8 or more substituted by one or more alkyl groups, and n is an integer from 5 to 15.)
[0030] As an implementation example, the composite core-shell particles may be composite core-shell particles having a cohesive energy of 10 mJ / g or less.
[0031] In one embodiment of the composite core-shell particles, the total surface energy of the particles may be less than 2000 mJ.
[0032] In one embodiment of the composite core-shell particles, the particle size of the core-shell particles may be 100 nm to 500 nm.
[0033] In one implementation example, the core weight of the composite core-shell particles may be 50 wt % to 95 wt %, preferably 60 wt % to 80 wt % of the total core-shell particles.
[0034] In one implementation example, the core-shell slurry may be an electrode-forming slurry comprising the core-shell particles and an electrode active material, or a composite comprising the particles.
[0035] One implementation example may also provide a battery prepared by using the core-shell particles as a binder for an electrode active material.
[0036] An embodiment of the composite core-shell particle is a composite core-shell particle having a perfluorinated resin core and a polymethyl methacrylate-based resin shell, and has a cohesive energy of 10 mJ / g or less and a total surface energy of 2000 mJ or less.
[0037] In one embodiment of the composite core-shell particles, the average diameter of the core-shell particles is 100 nm to 500 nm.
[0038] In an implementation example of the composite core-shell particles, the average diameter of the core of the core-shell particles is greater than or equal to 50 nm and less than 500 nm, and the thickness of the shell is 1 nm to 300 nm.
[0039] One implementation example may provide a water-dispersible slurry containing the composite core-shell particles.
[0040] An implementation example may provide a water-dispersible slurry, wherein the water-dispersible slurry further comprises an electrode active material.
[0041] Effects of the Invention
[0042] The core-shell polymer particles composed of the perfluorinated resin core and the polymethyl methacrylate-based resin prepared according to the preparation method of an implementation example can have excellent dispersion characteristics and minimize the generation of aggregates.
[0043] The core-shell type particles prepared by the preparation method according to an embodiment may have a large particle size of 100 nm to 500 nm, and the preparation method according to the present invention may prepare particles having excellent particle size uniformity.
[0044] The core-shell particles of one implementation example can provide core-shell particles with low cohesion energy and excellent dispersibility. For the core-shell particles, a powder rheometer (PowderRheometer) FT4 of Freeman Technology is used. After filling a sample tube with a diameter of 50 mm with core-shell resin, the impeller is rotated at a tip speed of 100 mm / sec and descended at the same time, and the total energy is measured 11 times. When the cohesion energy is measured during the ascending process, the specific energy (Specific energy) (cohesion energy) is less than 10 mJ / g, and the total energy (Total energy) is less than 2000 mJ.
[0045] Therefore, when the particles are mixed with other particles, they can be uniformly mixed due to their excellent dispersibility. When the particles are used as an adhesive, they can provide very uniform adhesive properties and the adhesive force can be easily adjusted according to the content.
[0046] In addition, core-shell particles having excellent properties, in which the shell layer uniformly covers the entire area of the core, can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is a TEM / EDS image of Example 1.
[0048] Figure 2 This is a TEM / EDS image of Comparative Example 2.
[0049] Figure 3 This is a TEM / EDS image of Comparative Example 2. DETAILED DESCRIPTION
[0050] The particle of the present invention is a core-shell particle having a core comprising a perfluoropolymer and a shell layer comprising a polymethyl methacrylate-based resin, providing a core-shell particle having a particle size of 100 nm to 500 nm and low cohesive energy.
[0051] For example, a core-shell structure including a perfluoropolymer core and a non-fluororesin shell is described in U.S. Pat. No. 6,841,594. However, the particles prepared by this method have high cohesion energy, so they actually coagulate in other inorganic particles or in a slurry state, resulting in a problem of insufficient dispersion. In other words, the cohesion energy is too high.
[0052] However, the core-shell particles of the present embodiment can adjust the particle size to a size of 100nm to 500nm and the size of the prepared particles is uniform, and can provide a core-shell particle with anti-agglomeration property as follows. Using the powder rheometer FT4 of Freeman Technology, after filling the core-shell resin in a sample tube with a diameter of 50mm, the impeller is rotated at a tip speed of 100mm / sec and descended at the same time, the total energy is measured 11 times, and when the agglomeration energy is measured during the ascending process, the specific energy (agglomeration energy) is less than 10mJ / g, and the total energy (Total energy) is less than 2000mJ.
[0053] Preferably, a core-shell particle having anti-agglomeration property can be provided, wherein the specific energy (agglomeration energy) is 6 mJ / g or less, and the total energy (Total energy) is 1200 mJ or less.
[0054] Furthermore, the core-shell particles of one embodiment can provide an excellent particle shape in which the shell layer uniformly covers the entire area of the core.
[0055] In one implementation example, the polymer or copolymer forming the core portion is not particularly limited as long as the monomer used to prepare the polymer or copolymer is a perfluorinated unsaturated monomer. For example, it can be prepared from a monomer selected from tetrafluoroethylene (TFE), perfluoro(alkyl vinyl ether) and hexafluoropropylene, and the resin forming the shell can be a polymethyl methacrylate-based resin.
[0056] In one embodiment, the polymer constituting the core of the core-shell particles can be a polymer or copolymer containing more than 90% or all of perfluorinated unsaturated monomers, and the polymethyl methacrylate-based resin forming the shell can contain more than 50 weight %, more than 60 weight %, more than 70 weight %, more than 80 weight %, more than 90 weight %, or 100 weight % of methyl methacrylate monomers.
[0057] Examples of the perfluorinated polymer forming the core portion may be polytetrafluoroethylene (PTFE), tetrafluoroethylene (TFE) / perfluoro(alkyl vinyl ether) copolymer (PFA) or TFE / hexafluoropropylene copolymer (FEP), but are not limited thereto, and in terms of physical properties, PTFE homopolymer is more preferred, but is not limited thereto.
[0058] In one implementation example, the core material can be synthesized, but when the MMA-based acrylic monomer is added to a perfluorinated resin slurry such as a commercially available PTFE aqueous solution slurry and emulsification polymerization is carried out using the emulsifier of the chemical formula 1, core-shell particles with significantly reduced cohesive properties and a uniform particle size of 100 nm to 500 nm to be obtained in the present invention can also be obtained.
[0059] When the perfluorinated resin slurry is prepared by polymerization, it can be prepared by appropriately mixing the perfluorinated unsaturated monomer and additives (polymerization initiator, etc.) and performing emulsion polymerization, solution polymerization, suspension polymerization, or other conventionally known methods.
[0060] The resin forming the shell is prepared by containing 50% by weight or more of a methyl methacrylate-based resin, preferably, 70% by weight or more of a methyl methacrylate monomer. As for the copolymer containing the monomer, there is no particular limitation on the comonomer, for example, it is preferably one or more selected from acrylonitrile, vinyl acetate, a styrene-based monomer, vinyl chloride, acrylate, vinylidene chloride, acrylic acid, methacrylic acid, and the like.
[0061] Next, a method for preparing core-shell particles according to an embodiment will be described.
[0062] In one embodiment, the preparation method of the perfluorinated resin core-polymethyl methacrylate-based shell particles can be: adding an emulsifier of the following chemical formula 1 to a perfluorinated resin slurry solution and dispersing or emulsifying it, and then adding MMA or a monomer composition with MMA as the main component and performing emulsification polymerization to prepare it.
[0063] [Chemical formula 1]
[0064] R-(-O-C2H4-) n -OH
[0065] (Wherein, in the chemical formula, R is an alkyl group of C8 or more substituted by one or more alkyl groups, and n is an integer from 5 to 15.)
[0066] As an implementation example, the R may be C8 to C 30 An alkyl group substituted with one or more alkyl groups.
[0067] In the chemical formula 1, when the ratio of the molecular weight of the oxyethylene group as the hydrophilic group to the total molecular weight ([oxyethylene chain molecular weight] / [total molecular weight]) is in the range of 0.5 to 1.0, it has a lower cohesive energy value and is therefore more preferred, but is not limited thereto.
[0068] An example of the Chemical Formula 1 may be the following Chemical Formula 2.
[0069] [Chemical formula 2]
[0070]
[0071] Hereinafter, the method for preparing the core-shell particles will be described in detail.
[0072] As an example, the preparation method can be obtained by adding methyl methacrylate or a monomer containing methyl methacrylate as a main component to a perfluorinated resin syrup, and polymerizing the syrup in the presence of an emulsifier of the chemical formula 1.
[0073] Before starting the polymerization, MMA or a monomer composition containing MMA as a main component may be completely added to the perfluorinated resin slurry for polymerization, or the monomer or monomer composition may be added continuously or stepwise for polymerization. However, in order to make the particle size uniform, the continuous addition method may be more preferred.
[0074] The emulsifier of the chemical formula 1 can be used alone or mixed with other emulsifiers. Although it is better to use it alone in reducing the cohesive energy, it can be used in a mixed manner from the perspective of properly adjusting the cohesive energy.
[0075] The emulsifier may be added to the perfluorinated resin particle slurry together with the monomer continuously or intermittently, or the emulsifier may be added in advance and then the monomer is added.
[0076] The content of the emulsifier of Chemical Formula 1 may be 0.05 to 10 parts by weight, 0.1 to 6 parts by weight, or 0.5 to 2 parts by weight relative to 100 parts by weight of the particles composed of the perfluoropolymer, but may be adjusted according to the size of the particles, and is not limited thereto.
[0077] In addition, as an implementation example, during the emulsion polymerization, a chain transfer agent, a chelating agent, a pH adjuster, etc. may be added as needed.
[0078] For example, the chain transfer agent may include, but is not limited to, mercaptans such as n-octyl mercaptan, n-dodecyl mercaptan, and tert-dodecyl mercaptan. The content of the chain transfer agent is not limited, but may be, for example, 0.001 to 2 parts by weight relative to 100 parts by weight of the monomer or monomer mixture.
[0079] For example, during the emulsion polymerization, the polymerization temperature may be, for example, 5° C. to 100° C., preferably 30° C. to 80° C., and the polymerization time may be 1 hour to 24 hours, but is not limited thereto.
[0080] As an implementation example, the solid content of the core-shell slurry polymerized in the core-shell shape can be 5 wt % to 60 wt %, 10 wt % to 50 wt %, 20 wt % to 40 wt % or values therebetween, but this can be selected as needed and is therefore not limited thereto.
[0081] As an example, the core-shell slurry is preferably an aqueous slurry. Of course, when it only means dispersion in water, it is more environmentally friendly, but as needed, it may also contain a water-miscible solvent. This mixed solvent may include one or more mixed solvents selected from polar ethers (ketones, acetone, alkyl esters, N-methylpyrrolidone and tetrahydrofuran, etc.), carbonates (diethyl carbonate, etc.), etc., but is not limited thereto.
[0082] As an example, the average diameter of the perfluorinated resin particles contained in the perfluorinated resin slurry forming the core portion can be 50 nm or more, 100 nm or more, 150 nm or more, 200 nm or more, 250 nm or more, 300 nm or more, 350 nm or more, 400 nm or more, 450 nm or more, less than 500 nm, and the size between the above numbers. The particle size having the above diameter can be measured by diluting the polymerized latex slurry by 1000 and using NICOMP 380 (Entegris, dynamic light scattering method) to measure the particle size and distribution.
[0083] In one implementation example, the core weight of the composite core-shell particles may be 50 wt % to 95 wt %, preferably 60 wt % to 80 wt % of the total core-shell particles.
[0084] In one implementation example, the shell layer may have a thickness of 1 nm to 300 nm, preferably 5 nm to 200 nm, and more preferably 10 nm to 150 nm. When the thickness is within the above range, it is preferred because it can exhibit excellent electrical properties when used as a battery material with dispersibility and low cohesion.
[0085] There is no particular limitation on the radius of the core and the thickness of the shell. For example, the radius of the core and the thickness of the shell may be 1:0.01 to 1, or 1:0.05 to 0.6. However, as long as the purpose of the present invention can be achieved, there is no particular limitation.
[0086] The core-shell particles can also be used in electrode binders or processing fluidizers for secondary batteries or latex paints.
[0087] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples. However, the following Examples and Comparative Examples are merely examples provided for describing the present invention in more detail, and the present invention is not limited to the following Examples and Comparative Examples.
[0088] The physical property evaluation method of the present invention is as follows.
[0089] 1. Determination of total solid content
[0090] 15 g of the polymerized slurry was weighed in an aluminum dish, and then dried in an oven at 80° C. for 24 hours, and the remaining weight was measured. The total solid content was calculated as follows: (weight after drying-weight of the dish) / initial weight×100.
[0091] 2. Non-fluorine resin extraction method
[0092] 100g of the completed polymerized slurry was placed in a 250ml centrifuge tube and centrifuged at 9000rpm for 30 minutes. The separated supernatant was discarded, 100g of acetone was added to the remaining solids, and the oscillator was vibrated for 3 hours to extract the non-fluorine resin with acetone. After oscillation for 3 hours, the fluorine resin was centrifuged at 9000rpm for 30 minutes again, and the fluorine resin gathered at the bottom, thereby separating the acetone supernatant dissolved with the non-fluorine resin separately. The supernatant dissolved with the separated non-fluorine resin was added dropwise to 400g of methanol to obtain the precipitated non-fluorine resin. The precipitated non-fluorine resin was separated using a vacuum filter, and after washing 3 times with methanol, it was loaded into a separate beaker and dried in an oven at 80°C for 24 hours.
[0093] 3. Weight average molecular weight (Mw) [kg / mol]
[0094] In order to determine the molecular weight of the non-fluorine-based resin of the slurry prepared in the examples and comparative examples, 10 mg of the extracted non-fluorine-based resin was dissolved in 10 ml of tetrahydrofuran (THF), and then filtered using a 0.2 μm Teflon filter, and then measured using gel permeation chromatography (GPC) of Waters.
[0095] 4. Glass transition temperature (Tg) [℃]
[0096] The non-fluorine-containing resin extracted from the slurry prepared in the examples and comparative examples was measured using TA's Q20 differential scanning calorimetry (DSC) for two cycles at a temperature increase of 10°C per minute. The glass transition temperature was calculated using the half conformal prediction (half CP) method using the inflection point of the second cycle.
[0097] 5. Determination of the ratio of fluorine resin to non-fluorine resin
[0098] 15 g of the slurry after the polymerization was placed in an aluminum pan and dried in an oven at 80° C. 10 mg of the dried powder was heated to 600° C. at a rate of 10° C. per minute by TGA to measure the weight loss. First, the ratio of the fluorine-based resin to the non-fluorine-based resin was measured by the degree of weight loss using the characteristics of the thermally decomposed non-fluorine-based resin.
[0099] 6. Particle size determination
[0100] The polymerized latex was diluted 1000 times, and the particle size and distribution were measured using NICOMP 380 (Entegris, dynamic light scattering).
[0101] 7. Determination of total energy of fluidity and condensation energy (specific energy)
[0102] After the completed polymerization slurry is freeze-dried, it is obtained in powder form and the fluidity and cohesion energy are measured by the FT4 Powder Rheometer of Freeman Technology. After the resin is filled into a sample tube with a diameter of 50 mm, the impeller is rotated at a tip speed of 100 mm / s and descended at the same time. The total energy is measured 11 times, and the cohesion energy is measured during the ascending process. When the specific energy value is less than 5, it is judged as low cohesion, when it exceeds 5 and is less than 10, it is judged as moderate cohesion, and when it exceeds 10, it is judged as high cohesion. Under the premise of normal operation of the equipment, the measurement results of total energy and specific energy are taken as the average of 8 times.
[0103] 8. Particle structure analysis (TEM / EDS)
[0104] After plasma treatment on a transmission electron microscope (TEM) grid, a drop of slurry was dropped and then dried at room temperature. The dried sample was analyzed for structure using TEM / EDS (TECHNAI TF20 from FEI) at an accelerating voltage of 200 kV.
[0105] [Example 1]
[0106] A PTFE aqueous dispersion having an average particle diameter of 0.21 μm, a solid content of 30%, and a standard specific gravity (SSG) of 2.16 to 2.22 was prepared. Then, 2448.0 g of the PTFE dispersion and 48.96 g of a 90% aqueous solution of polyethylene glycol trimethylnonyl ether having a molecular weight of 384 g / mol of ethylene glycol repeating units showing hydrophilicity were added to a 4-liter reactor, and nitrogen was bubbled while stirring at a speed of 350 RPM and the temperature was raised to 75°C.
[0107] After reaching the polymerization temperature of 75°C, nitrogen bubbling was stopped, and 15 minutes later, 183.86 g of a monomer mixture consisting of 146.88 g of methyl methacrylate (MMA), 36.72 g of butyl acrylate (nBA) and 0.26 g of n-octyl mercaptan was added dropwise into the reactor over 15 minutes.
[0108] 15 minutes after the monomer mixture was added, 68.4 g of distilled water and 0.92 g of potassium persulfate aqueous solution were added dropwise to the reactor over about 10 minutes. After the addition of potassium persulfate was completed, the polymerization reaction was carried out for 3 hours and then cooled to 30° C. to obtain a white emulsion.
[0109] The size analysis of the white emulsion was performed by NiCOMP and is shown in Table 1. The particle structure analysis results are shown in Figure 1 In. Figure 1 As shown, it can be seen that the polymethyl methacrylate shell is uniformly formed on the entire surface of the core, and the particle size is also very uniform.
[0110] In addition, the emulsion was freeze-dried for 72 hours at -60°C and 10 mTorr to obtain a white powder, and the results of total energy and specific energy measured using the white powder are shown in Table 1. The results showed that the specific energy (mJ / g) was very low at 5.8, and the total energy was also very excellent at 1150 mJ (less than 2000 mJ).
[0111] [Comparative Example 1]
[0112] The PTFE aqueous slurry used in Example 1 was directly freeze-dried without additional polymerization, and then the total energy and specific energy were measured using the FT4 of Freeman Technology. The results are shown in Tables 1 and Figure 2 The freeze-dried product of the PTFE aqueous dispersion was interrupted due to excessive load under the set test conditions, so the data was calculated using the measured value once. The results are shown in Table 1.
[0113] [Comparative Example 2]
[0114] The same contents were used except that sodium dodecyl benzene sulfonate was used instead of the emulsifier in Example 1. The results of TEM electron microscopy of the aggregates are shown in FIG. Figure 2 and Figure 3 In Figure 2 As shown in FIG. 1 , it is observed that the particles are not core-shell shaped but irregularly shaped, wherein it can be seen that the polymethyl methacrylate fails to cover the entire surface of the fluoropolymer as the core, and as shown in FIG. Figure 3 As shown, the particle size is also irregular and non-uniform, and the particle size is also small. The results of the analytical properties are shown in Table 1 below.
[0115] [Comparative Example 3]
[0116] In Example 1, the same method was used except that 48.96 g of a 90% aqueous solution of polyethylene glycol n-nonyl ether having a molecular weight of 384 g / mol of ethylene glycol repeating units was added as an emulsifier. As a result, aggregates were observed, and the results of analytical properties are shown in Table 1 below.
[0117] [Comparative Example 4]
[0118] In Example 1, the same method was used except that the emulsifier having a repeating unit of ethylene glycol unit of 3 was used instead of a 90% aqueous solution of polyethylene glycol trimethyl nonyl ether having a molecular weight of 384 g / mol as the repeating unit of ethylene glycol. The results are shown in Table 1.
[0119] Table 1
[0120]
[0121]
[0122] From the analysis results, it can be seen that Figure 1 As shown, Example 1 of the present invention has a particle size of 260 nm and has uniform particles, a very low specific energy (mJ / g) of 5.8, and also exhibits very excellent total energy of 1150 mJ (less than 2000 mJ).
[0123] On the contrary, it can be seen that when the material of the present invention is not used as an emulsifier (Comparative Examples 2 and 3) or the structure defined in the present invention is not included (Comparative Example 4), and the repeating unit of ethylene glycol in Example 2 is short, the specific energy (mJ / g) becomes worse and is greater than 10 and greater than 15, and the total energy is greater than 2000mJ, greater than 3000mJ, and greater than 4000mJ, that is, it shows very low dispersibility.
Claims
1. A slurry of composite core-shell particles, wherein: The composite core-shell particles have a perfluorinated resin core and a polymethyl methacrylate-based resin shell layer. In the perfluorinated resin particle slurry, the composite core-shell particle slurry is prepared by emulsifying and polymerizing acrylic acid monomers using a polyethylene glycol ether having a C8 or higher alkyl group substituted with one or more alkyl groups of the following chemical formula 1 as an emulsifier, [Chemical formula 1] R-(-O-C2H4-) n -OH In the chemical formula, R is an alkyl group of C8 or higher substituted with one or more alkyl groups, and n is an integer of 5 to 15.
2. The slurry of composite core-shell particles according to claim 1, wherein In the Chemical Formula 1, a ratio of a molecular weight of an oxyethylene group as the hydrophilic group to a total molecular weight ([oxyethylene chain molecular weight] / [total molecular weight]) is 0.5 to 1.
0.
3. The slurry of composite core-shell particles according to claim 1, wherein The chemical formula 1 is an emulsifier of the following chemical formula 2, [Chemical formula 2] 4. The slurry of composite core-shell particles according to claim 1, wherein The perfluorinated resin particles are perfluorinated resin particles containing tetrafluoroethylene-derived units as a main component.
5. The slurry of composite core-shell particles according to claim 1, wherein The perfluorinated resin particles are perfluorinated resin particles containing tetrafluoroethylene-derived units as a main component.
6. A composite core-shell particle, wherein: The composite core-shell particles have a perfluorinated resin core and a polymethyl methacrylate-based resin shell. The composite core-shell particles are prepared by emulsifying and polymerizing acrylic acid monomers in a perfluorinated resin particle slurry using a polyethylene glycol ether having a C8 or higher alkyl group substituted with one or more alkyl groups of the following Chemical Formula 1 as an emulsifier, [Chemical formula 1] R-(-O-C2H4-) n -OH In the chemical formula, R is an alkyl group of C8 or higher substituted with one or more alkyl groups, and n is an integer of 5 to 15.
7. The composite core-shell particle according to claim 6, wherein The composite core-shell particles have a cohesive energy of 10 mJ / g or less.
8. The composite core-shell particle according to claim 6, wherein The total surface energy of the composite core-shell particles is less than 2000 mJ.
9. The composite core-shell particle according to claim 6, wherein The core-shell particles have an average diameter of 100 nm to 500 nm.
10. The composite core-shell particle according to claim 1, wherein The weight of the core of the composite core-shell particle is 50 wt % to 95 wt % of the total core-shell particle.
11. An electrode, wherein: The electrode is prepared from a composite comprising the composite core-shell particle according to any one of claims 6 to 10 and an electrode active material.
12. A battery, wherein: The composite core-shell particles according to any one of claims 6 to 10 are contained as a binder.
13. The composite core-shell particle according to claim 6, wherein The composite core-shell particles having a perfluorinated resin core and a polymethyl methacrylate-based resin shell have a cohesive energy of less than 10 mJ / g and a total surface energy of less than 2000 mJ.
14. The composite core-shell particle according to claim 13, wherein The average diameter of the composite core-shell particles is 100 nm to 500 nm.
15. The composite core-shell particle according to claim 13, wherein The average diameter of the core of the composite core-shell particle is greater than or equal to 50 nm and less than 500 nm, and the thickness of the shell is 1 nm to 300 nm.
16. A composite, wherein Comprising the particles according to any one of claims 12 to 15.
17. The composite according to claim 16, wherein The composite contains an electrode active material.
Citation Information
Patent Citations
Core-shell fluoropolymer dispersions
US6841594B2
Fluoropolymer emulsion
JP2010534740A
Binder particles for electrochemical element
KR1020120094003A
Core-shell fluoropolymer particles useful for weatherable coating of backsheet in photovoltaic modules
KR1020120103856A
Acrylic copolymer latex, preparation method thereof, and vinyl chloride resin composition comprising the same
KR1020150142906A